Matchmaking can be murder - Flower, Amanda (Flower, Amanda, Amish matchmaker mystery., 2020)
When widowed Millie Fisher moves back to her childhood home of Harvest, Ohio, she notices one thing right away<U+2014>the young Amish are bungling their courtships and marrying the wrong people! A quiltmaker by trade, Millie has nevertheless stitched together a few lives in her time, with truly romantic results. Her first mission? Her own niece, widowed gardener Edith Hochstetler, recently engaged to rude, greedy Zeke Miller. Anyone can see he<U+2019>s not right for such a gentle young woman<U+2014>except Edith herself. Pleased when she convinces the bride-to-be to leave her betrothed before the wedding, Millie is later panicked to find Zeke in Edith<U+2019>s greenhouse<U+2014>as dead as a tulip in the middle of winter. To keep her niece out of prison<U+2014>and to protect her own reputation<U+2014>Millie will have to piece together a patchwork of clues to find a killer, before she becomes the next name on his list . . .